2019
DOI: 10.1002/ajh.25657
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic score predicts outcomes in newly diagnosed multiple myeloma patients

Abstract: Risk stratification of multiple myeloma (MM) at diagnosis is critical. We examined the ability of hematopoietic indices including mean corpuscular volume (MCV), hemoglobin (Hgb), and platelet (Plt) to predict outcomes. This was a retrospective study of patients treated at Mayo Clinic between January 2004 and April 2018. We incorporated three variables (Hgb < 10 g/dL, Plt < 150 × 10 9 /L, and MCV > 96 fL), assigning a score of 1 to each. We identified 1540 newly diagnosed MM patients, of whom 707 (46%) had a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…In an early Mayo clinic study (with patients enrolled from 1985 to 1988), it was found that a Hgb level < 100 g/L and a Plt count < 150×10 9 /L were predictive of relatively worse outcomes based on univariate analysis (2). In 2020, clinical data of MM patients treated at the Mayo Clinic in the United States for more than 10 years were retrospectively analysed (11), and propose the in uence of hematopoietic score composed of Hgb level, MCV and plt count on the prognosis of MM patients, which con rmed that patients with high hematopoietic scores tend to have a worse prognosis. However, those data were obtained for patients in the previous era of traditional chemotherapy, less than 45% of the patients in this group were treated with a proteasome inhibitor and/or immunomodulator-based regimen; therefore, the prognostic signi cance of the hematopoietic score needs further con rmation in the era of new drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an early Mayo clinic study (with patients enrolled from 1985 to 1988), it was found that a Hgb level < 100 g/L and a Plt count < 150×10 9 /L were predictive of relatively worse outcomes based on univariate analysis (2). In 2020, clinical data of MM patients treated at the Mayo Clinic in the United States for more than 10 years were retrospectively analysed (11), and propose the in uence of hematopoietic score composed of Hgb level, MCV and plt count on the prognosis of MM patients, which con rmed that patients with high hematopoietic scores tend to have a worse prognosis. However, those data were obtained for patients in the previous era of traditional chemotherapy, less than 45% of the patients in this group were treated with a proteasome inhibitor and/or immunomodulator-based regimen; therefore, the prognostic signi cance of the hematopoietic score needs further con rmation in the era of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Hgb in the prognosis of MM patients is clearly de ned in the Durie-Salmon staging system and 100 g/L is used as one of the cut-off values for an abnormal Hgb level (6). In addition, abnormal red blood cell size, indicated by abnormal red blood cell distribution width (RDW) or average red blood cell volume values, and Plt counts are important MM prognostic indicators (2,6,(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…An increased red blood cell volume is often an indication of folic acid or vitamin B12 de ciency; however, it is regrettable that only a few patients in our group were tested for serum vitamin levels, with no de ciency found. According to the literature, vitamin B12 de ciency has been reported in approximately 13-20% of patients with plasma cell disease (9,16,17). Regardless, this may not be related to macrocytosis in these patients, and some patients with vitamin B12 de ciency do not show an increase in their MCV (9,16).…”
Section: Multivariate Analysis Using Thementioning
confidence: 99%
“…According to the literature, vitamin B12 de ciency has been reported in approximately 13-20% of patients with plasma cell disease (9,16,17). Regardless, this may not be related to macrocytosis in these patients, and some patients with vitamin B12 de ciency do not show an increase in their MCV (9,16). It is believed that increased an erythrocyte volume is more common in elderly patients, which may be related to the shortened erythrocyte life span and the emergence of more new erythrocytes (reticulocytes) to replace the lost red blood cells, resulting in a slightly larger volume (18) and an increased peripheral blood red blood cell distribution width (12,19).…”
Section: Multivariate Analysis Using Thementioning
confidence: 99%
See 1 more Smart Citation